2017
DOI: 10.11648/j.ajls.20170501.12
|View full text |Cite
|
Sign up to set email alerts
|

Phytoecdysteroids: Isolation and Biological Applications

Abstract: Phytoecdysteroids are analogues of arthropod steroid hormones found in plants, where they deter predation by non-adapted predators. Their discovery in several plant species displayed a wide array of rather beneficial agricultural impact. An overview is given on both well-known and recently discovered phytoecdyteroids including a sophisticated isolation scheme and notable physiological and pharmacological effects of ecdysteroids on vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Thus, the positive effect of the application of phytoecdysteroid-containing cream in SD patients may be associated with the normalization of the keratinocytes differentiation process. It is postulated [ 34 , 35 ] that ecdysones may have a significant impact on the reduction of inflammation, probably due to their immunomodulatory function and the modulation of the level of the pro-inflammatory cytokine (e.g.,interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α)). Moreover, it has been reported that phytoecdysteroids improve skin quality by accelerating the healing of wounds and burns [ 36 , 37 ].Several studies [ 38 ] have claimed associations between Malassezia restricta lipase and SD.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the positive effect of the application of phytoecdysteroid-containing cream in SD patients may be associated with the normalization of the keratinocytes differentiation process. It is postulated [ 34 , 35 ] that ecdysones may have a significant impact on the reduction of inflammation, probably due to their immunomodulatory function and the modulation of the level of the pro-inflammatory cytokine (e.g.,interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α)). Moreover, it has been reported that phytoecdysteroids improve skin quality by accelerating the healing of wounds and burns [ 36 , 37 ].Several studies [ 38 ] have claimed associations between Malassezia restricta lipase and SD.…”
Section: Resultsmentioning
confidence: 99%
“…39 The significant activity towards reducing inflammation might be due to its immunomodulatory function and modulation of proinflammatory cytokines (IL-6 and TNF-). 40 …”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, adult weevils did hardly accept spinach for feeding, which could be due to phytoecdysteroids contained in spinach leaves. Spinach is among the plants with the highest content of these substances (Grebenok et al 1994;Al Naggar et al 2017), which have previously been found to deter feeding of several Coleopteran species (Jurenka et al 2017).…”
Section: Discussionmentioning
confidence: 99%